Pancasila-Based Children's Story App: Reading Material for Grade IV Elementary School Students - Decenni Amelia; Isah Cahyani; Kama Abdul Hakam; Cepi Riyana (Al Ibtida: Jurnal Pendidikan Guru MI, 2024)
AbstractThis research aims to develop reading materials story child loaded profile student Pancasila based on mobile application which is a literacy media to help improve interest read students and complement the availability of resources reading which contains the values of the Pancasila lesson profile in story child on the dimension of independence, reasoning critical and creativity as supporters of the independent curriculum. The purpose of this study is to determine the development process and feasibility of products developed using the method study Design & Development. This research was conducted at State Elementary School (SDN) Bahagia 06 Bekasi City, West Java. The subjects of this research were expert material validators, media experts, practitioners and 26 fourth grade students. The research data collection techniques used interviews, observations, and documentation. The instruments used were validator questionnaires and student response questionnaires. as well as teacher response . The developed product was evaluated very well with a percentage of material experts of 96 % in the very feasible category , media experts 94% in the very feasible category, practitioner experts 95% in the very feasible category and student responses were very good. So, from the data obtained, materialreading story child loaded profile student Pancasila based on mobile applications on the dimensions of independence, reasoning critical thinking and creativity are very worthy of being used to help improve interest read students and complement the availability of resources readingwhich contains the values of the Pancasila lesson profile as Supporter curriculum independent.Keywords: materials reading, children's stories, mobile applications.AbstrakPenelitian ini bertujuan untuk mengembangkan bahan bacaan cerita anak bermuatan profil pelajar Pancasila berbasis aplikasi mobile sebagai media literasi untuk membantu meningkatkan minat baca siswa dan melengkapi ketersediaan sumber bacaan yang mengandung nilai-nilai profil pelajar Pancasila dalam cerita anak pada dimensi kemandirian, penalaran kritis, dan kreativitas sebagai pendukung kurikulum merdeka. Tujuan dari penelitian ini adalah untuk mengetahui proses pengembangan dan kelayakan produk yang dikembangkan menggunakan metode penelitian Design & Development. Penelitian ini dilaksanakan di SDN Bahagia 06 Kota Bekasi, Jawa Barat. Subjek penelitian ini adalah validator ahli materi, ahli media, praktisi, dan 26 siswa kelas empat. Teknik pengumpulan data dalam penelitian ini menggunakan wawancara, observasi, dan dokumentasi. Instrumen yang digunakan adalah kuesioner validator serta kuesioner tanggapan siswa dan guru. Produk yang dikembangkan dievaluasi dengan sangat baik dengan persentase ahli materi sebesar 96% dalam kategori sangat layak, ahli media 94% dalam kategori sangat layak, ahli praktisi 95% dalam kategori sangat layak, dan tanggapan siswa sangat baik. Jadi, dari data yang diperoleh, bahan bacaan cerita anak bermuatan profil pelajar Pancasila berbasis aplikasi mobile pada dimensi kemandirian, penalaran kritis, dan kreativitas sangat layak digunakan untuk membantu meningkatkan minat baca siswa dan melengkapi ketersediaan sumber bacaan yang mengandung nilai-nilai profil pelajar Pancasila sebagai pendukung kurikulum merdeka.Kata kunci: bahan bacaan, cerita anak, aplikasi mobile.